1993
DOI: 10.1037/0022-0167.40.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Preference for and comfort with male versus female counselors among sexually abused girls in individual treatment.

Abstract: Twenty sexually abused girls, ages 7 to 15 years, received 6 sessions of psychoeducationally based individual counseling from either male (n = 10) or female (n = 10) counselors. Clients' pretreatment and posttreatment preference for sex of their counselor and the girls' anticipated comfort with male versus female counselors were analyzed, as was clients' posttreatment actual comfort with their counselors. Analyses of covariance, with pretreatment data as the covariate, revealed that participants treated by mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…The studies by Fowler et al 641,642 examined the acceptability of counsellor gender for treatment for sexual abuse. Kilcrease-Fleming et al 643 also investigated counsellor gender using a standardised rating scale of video-taped interviews analysing differences in verbalisation between male and female counsellors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies by Fowler et al 641,642 examined the acceptability of counsellor gender for treatment for sexual abuse. Kilcrease-Fleming et al 643 also investigated counsellor gender using a standardised rating scale of video-taped interviews analysing differences in verbalisation between male and female counsellors.…”
Section: Methodsmentioning
confidence: 99%
“…The other studies 176,638,[641][642][643]645,646,674,677 were uncontrolled designs, each using a purposive sample of those engaged in treatment. The studies by Fowler et al 641,642 examined the acceptability of counsellor gender for treatment for sexual abuse.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to psychotherapy research, some female clients prefer a woman therapist to a man therapist [31] . Some studies have reported that women attending female therapists commit better than women attending male therapists [32] , although opposite findings have been reported [11,33] .…”
mentioning
confidence: 99%